1997
DOI: 10.1074/jbc.272.11.6965
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Polysaccharides from the Egg Jelly Layer Are Species-specific Inducers of Acrosomal Reaction in Sperms of Sea Urchins

Abstract: We have characterized the fine structure of sulfated polysaccharides from the egg jelly layer of three species of sea urchins and tested the ability of these purified polysaccharides to induce the acrosome reaction in spermatozoa. The sea urchin Echinometra lucunter contains a homopolymer of 2-sulfated, 3-linked ␣-L-galactan. The species Arbacia lixula and Lytechinus variegatus contain linear sulfated ␣-L-fucans with regular tetrasaccharide repeating units. Each of these sulfated polysaccharides induces the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(125 citation statements)
references
References 27 publications
3
122
0
Order By: Relevance
“…These findings also suggest a therapeutic use of CS to control the IgE mediated allergic response. The number and position of O-sulfo groups varies among CS samples obtained from different sources (Alves et al, 1997;Farias et al, 2000;Santos et al, 1992).We hypothesized that the immunological activity of orally administered CS might also be different among the several types of CS. Thus, it is important to determine the structure-activity relationship (SAR) of CS, particularly with respect to the number and position ofO-sulfo groups in CS.…”
Section: A New Concept For Explaining the Effect Of Chondroitin Sumentioning
confidence: 94%
“…These findings also suggest a therapeutic use of CS to control the IgE mediated allergic response. The number and position of O-sulfo groups varies among CS samples obtained from different sources (Alves et al, 1997;Farias et al, 2000;Santos et al, 1992).We hypothesized that the immunological activity of orally administered CS might also be different among the several types of CS. Thus, it is important to determine the structure-activity relationship (SAR) of CS, particularly with respect to the number and position ofO-sulfo groups in CS.…”
Section: A New Concept For Explaining the Effect Of Chondroitin Sumentioning
confidence: 94%
“…Thus modifications of the anuran egg extracelmoieties mediate sperm-zona pellucida interaction in mice [2], lular matrix are fundamental processes that regulate sperm-egg hamsters [3], and rats [4]. Alves et al [5] have shown that sul-interaction in fertilization. fated polysaccharides from the egg jelly of Sea urchins are spe-…”
mentioning
confidence: 99%
“…Among all the MSP with well-defined chemical structures described so far (Figures 1 and 2), there is a single description from the body wall of the sea cucumber ( Figure 1A) (Mulloy et al, 2004), a few examples of SG isolated from the tunic of ascidians ( Figure 2C and 2D) (Mourão & Perlin, 1987;Santos et al, 1992;Pavão et al, 1998), and some reports from specific red algal cell walls ( Figure 2E) (Pereira et al, 2005;Fonseca et al, 2008). All of the remaining structures ( Figure 1B -H and 2A and B) belong to the egg jelly coat of sea urchins (Alves et al, 1997;Alves et al, 1998;Vilela-Silva, et al, 1999;Vilela-Silva et al, 2002;Mulloy et al, 2004) The body of some species of ascidians also contains peculiar GAG that show sulfation patterns distinct from mammalian GAG (Pavão et al, 1995;Pavão et al, 1998), as exemplified by the tunicate dermatan sulfates (DS) in Figure 2F.…”
Section: The Trends For Regular Chemical Structures In Invertebrates mentioning
confidence: 99%
“…The MSP with well-defi ned chemical structures (SF, SG and GAG in Figures 1 and 2) are extracted from echinoderms (Echinodermata) like sea cucumbers (Mulloy et al, 2004); (B) Lytechinus variegatus (Alves et al, 1997); (E) Strongylocentrotus purpuratus-I (Stimpson, 1857) (Alves et al, 1998) Vilela-Silva et al, 2002); and (H) Strongylocentrotus franciscanus (A. Agassiz, 1863) Vilela-Silva et al, 1999). (Castro et al, 2009) (Santos et al, 1992) (Mourão & Perlin, 1987); (E) both Botryocladia occidentalis (Kylin, 1931) and Gelidium crinale (Gaillon 1828) express [3-β-D-Galp-1→4-α-Gal-1→] n with different sulfation contents (Pereira et al, 2005;Fonseca et al, 2008); and (F) the DS from Styela plicata, Halocynthia pyriformis (Rathke, 1806), and Ascidian nigra (Savigny, 1816) are composed of [4-α-L-IdoA-1→3-β-D-GalNAc-1] n with also different sulfation patterns (Pavão et al, 1995;Pavão et al, 1998).…”
Section: The Trends For Regular Chemical Structures In Invertebrates mentioning
confidence: 99%